Inflammation and Comorbidity. Are There any Chances to Improve the Prognosis in Patients with Extremely High Cardiovascular Risk? - M. V. Zykov; O. L. Barbarash (Рациональная фармакотерапия в кардиологии, 2021)
The review contains actual data on possible approaches aimed at improving the prognosis in a special category of patients with extremely high cardiovascular risk, as well as in patients with recent acute coronary syndrome combined with comorbidity, including multifocal atherosclerosis. Currently, there are no class I recommendations for such patients aimed at reducing the risk of adverse cardiovascular events. It is suggested that suppression of inflammation may be a new therapeutic goal in this category of patients. Given the importance of inflammation in the development and course of atherosclerosis, in recent years there have been repeated attempts to influence the various components of the pro-inflammatory cascade involved in atherogenesis, but not all of them have been successful. Special attention is given to the anti-inflammatory effects of colchicine, a drug that can improve cardiovascular outcomes in patients with proven atherosclerosis. The review provides numerous pathogenetic and clinical evidence for the effectiveness of colchicine in patients with various manifestations of atherosclerosis. It is concluded that colchicine is the most promising anti-inflammatory drug that can improve the outcome of cardiovascular diseases. Thus, there is a need to initiate new clinical trial protocols aimed at studying the anti-inflammatory potential of this drug in patients with extreme cardiovascular risk.